Experimental investigations of oxyfuel burner for cement production application. (15th January 2019) - Carrasco, Francisco; Grathwohl, Simon; Maier, Jörg; Ruppert, Johannes; Scheffknecht, Günter
Highlights: Burner design with single nozzles is adequate for oxyfuel operation in a cement application. Oxygen enrichment in primary gas is a new variable for burner configuration and can be used to improve fuel ignition. Total oxygen concentration in combustion gas can be adjusted to obtain similar air-firing temperature profile. Abstract: The production of cement is one of the CO2 intensive processes, due to the inherent formation of CO2 in the calcination process by decomposition of limestone which is additional to the CO2 generated from fuel combustion. Carbon capture and storage technologies have been seen as a promising way to comply with CO2 reduction targets. As part of the objectives of the Horizon 2020 project CEMCAP, the retrofitting of key parts of the equipment of a conventional cement plant to oxyfuel combustion are investigated. The present study reports the results of several combustion tests employing a downscaled commercial kiln burner to determine its adequacy for oxyfuel operation mode. The investigations were carried out in the 500 kWth top-fired combustion facility at University of Stuttgart, which was previously adapted for these tests, including the installation of an electric preheating system to rise secondary gas temperature up to 800 °C. Fuel used is a German pre-dried lignite previously milled to required fineness in a separate location. A variety of in-flame measurements are performed at a dozen of ports located at different distances from burner outlet in order to characterize combustion behavior in each firing mode. It was observed that under oxyfuel mode additional parameters in burner configuration like total oxygen concentration and oxygen distribution in primary and secondary gas are key variables to adjust flame formation and obtain similar results as in conventional air firing.